Analisis Semiotika Pada Desain Logo Penerbit Cahaya_Publisher - Wingki Azwandi Saputra; Fifi Hasmawati; Manalullaili (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research is entitled "Semiotics Analysis on the Design of the Cahaya_Publisher Publisher Logo". This research was conducted on the logo of the Cahaya_Publisher publisher, which is a book publishing that focuses on the religious/spiritual genre. The formulation of the problem in this study is the semiotic analysis of the Cahaya_publisher logo design on the meaning of connotations, denotations and myths in the Cahaya-publisher logo design. The purpose of this study is to determine the meaning of connotations, denotations, and myths in the logo design of the Cahaya_publisher publisher. The author uses a qualitative research method, the data used is primary data in this study, namely the founder of Cahaya_publisher who also designed the Cahaya_publisher logo and secondary data, namely printed media and internet sites to support collecting data sources. Data collection techniques were carried out by interviews and documentation. The analysis technique used is Roland Barhets Semiotics analysis. The results of this study are that the meaning of denotation is a visual unity of the yellow and brown logo with the use of sunflower and pen elements. writing, for myth is a positive hope that is contained in the logo design in the form of a sunflower unity and the colors yellow and brown are chosen as representatives of sunlight which has positive energy, lighting for the surroundings in this case for the world of publishing and writing.